IMPLEMENTASI GOVERNANCE DI KEMENTERIAN PERINDUSTRIAN REPUBLIK INDONESIA DAN PENGARUHNYA TERHADAP KINERJA - Bayu Giri Prakosa; Y Anni Aryani (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2015)
This study examines whether governance principles implementation in The Ministry of Industry of Republic Indonesia has been well implemented. This study also tests the effect of the implementation on Industry Ministry’s performance using the Ministry of Industry’s performance indicators which have been stipulated by the Minister of Industry in the Rule of Ministry of Industry No: 41/MIND/PER/3/2010, which are: stakeholder perspective and implementation of functional perspective. The typology of governance quality from TUGI is used to measure the implementation of governance principles. Using data from the internet survey, this study shows that most of the governance principles (orderly implementation of state administration, public interest, proportionality, professionalism, and accountability) are have been implemented well. Yet, there are two governance principles that have not been well implemented; they are law enforcement and transparency. In addition, this study reveals that although the governance principles have been implemented well in the Ministry of Industry, its only public interest principle that has impact on performance. Keywords: governance principle, stakeholder perspective, implementation of functional perspective, performance, internet survey.